Modulation of immunity and barrier function in pre- and postnatal animal ontogenesis. Mechanisms of natural resistance in newborn piglets - Masjuk, D.; Masiuk, Dmytro; Masiuk, D. N.; Masiuk, D. M.; Masiuk, D.; Masyuk, D. N.; Masyuk, D. M.; Masyuk, D.; Masjuk, Dmytro; Masiuk, Dmytro M.; Masiuk, Dmytro Mykolayovych; Масюк, Дмитро Миколайович; et al. (Baltija Publishing, 2023)
At the time of birth, piglets form a complex of immunocompetence morphological markers at the tissue and cellular levels. After birth, their functional development is activated. The immune components activity in piglets during the first weeks of life has a downward trend. At the end of the suckling period, it changes to an upward trend due to the activation and intensification of their own immune system components. У момент народження у поросят формується комплекс морфологічних маркерів імунокомпетентності на тканинному та клітинному рівнях. Після народження їх функціональний розвиток активізується. Активність компонентів імунітету у поросят у перші тижні життя має тенденцію до зниження. Наприкінці підсисного періоду вона змінюється на висхідну за рахунок активації та посилення ланок власної імунної системи.
Модуляція імунітету та бар'єрної функції в пре- і постнатальному онтогенезі тварин. Механізми природної резистентності у новонароджених поросят
Масюк Дмитро Миколайович https://orcid.org/0000-0002-2800-2580 Недзвецький Віктор Станіславович https://orcid.org/0000-0001-8975-6952 Кокарєв Андрій Вікторович https://orcid.org/0000-0002-5673-5984
Keywords: imunna systema; імунна система; pryrodna rezystentnist; природна резистентність; imunitet; імунітет